COVID-19 Pandemic: Langkawi Vocational College Student Challenge in Using Google Classroom for Teaching and Learning (T&L) - W.A.S., Wan Hassan; Ariffin, Ahmad Hamdan; F., Ahmad; S.N.M., Sharberi; M. I., Nor Azizi; Zulkiflee, S.N. (WARSE, 2020)
The implementation of government-issued social awareness during the COVID-19 pandemic has affected the teaching and learning (T&L) activities. This study aims to identify the challenges that students face in using Google Classroom as a T&L method during the COVID-19 pandemic. A total of 39 Culinary Arts Diploma students at Langkawi Vocational College, Kedah who took the subjects of DHA1234 - Basic Food and Cookery, DHA 3051 - Final Year Project 1 and DHA 1123 - Introduction to Hospitality Industry participated in the study. The questionnaire used was adapted from the previous study and had received expert’s confirmation before being used in the study. The results of the study were analyzed using descriptive statistics involving average use, standard deviation, percentage, frequency, and score. Inferencial statistics involved pearson correlation tests. The study showed that the mean level of challenge faced by students in using Google Classroom is 3.46. Meanwhile, the pearson correlation test found that the significant value was .000. Therefore, there was a relationship between motivational and internet networks aspects. Therefore, the hypothesis (H0) stated in the hypothesis section was rejected.